MACROECONOMIC ANALYSIS OF THE REPUBLIC OF UZBEKISTAN FOR 2023 - Sherkhanov Iftikhor Abdulrazzokovich (Western European Studies, 2025)
This article provides a detailed analysis of the macroeconomic performance of the Republic of Uzbekistan in 2023. Drawing on data from official sources, it highlights growth in GDP, inflation control, trade activities, and investments. The analysis also examines sectoral contributions and challenges, offering insights into Uzbekistan’s economic trajectory and future potential.
Keywords: Macroeconomics; Uzbekistan; GDP Growth